Bioburden exposure in highly contaminated occupational environments - Viegas, Carla (2017)
The presence of high levels of bioaerosols is frequently the result of the natural colonization of an organic substrate present in the workplace. Therefore bioaerosol composition depends on the type of setting and materials that are handled/used. Each of the components has normally health-based recommended exposure limit but workers are normally exposed to the mixture present in the bioaerosols and this can implicate different and more severe health effects than being exposed to a singular component. The purpose of this chapter is to review the microbiota and metabolites concentrations found in occupational environments with high probability to contain high microbiota load. Additionally, It also addresses the most frequently encountered fungal and bacteria species, the sampling strategy selected and the measured metabolites and tasks involving high exposure. The review focuses on 43 articles that were considered relevant to this topic (scientific studies published between 1991 and 2017). It was possible to obtain relevant data regarding the settings and tasks that involve higher exposure to bioaerosols and highlighting also the future challenges to ensure a suitable exposure assessment of the microbiota burden.